1977
DOI: 10.1021/jm00214a018
|View full text |Cite
|
Sign up to set email alerts
|

Total synthesis of (.+-.)-1-carbacefoxitin and -cefamandole and (.+-.)-1-oxacefamandole

Abstract: The total syntheses of the (+/-)-1-carba analogues of cefoxitin (11), 7 alpha-methoxydeacetylcephalothin (5) and cefamandole (31) and the (+/-)-1-oxa analogue of cefamandole (43) are described. Their bioactivity spectra against 14 typical organisms are similar to those of their natural 1-thia counterparts, with the 1-carba compounds somewhat less active and the 1-oxa compound more active than the natural ones.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

1981
1981
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(18 citation statements)
references
References 1 publication
0
18
0
Order By: Relevance
“…In 1974 Cama, Christensen, and Guthikonda at Merck reported fully synthetic routes to "carbacephalosporin" and "oxacephalosporin" analogs replacing the sulfur atom within the bicyclic core of cephalothin (a first-generation cephalosporin), by a carbon atom and an oxygen atom, respectively (Figure 7). [102] Crucially, these fully synthetic analogs exhibited biological activity that was comparable to cephalothin.…”
Section: Antibacterial Drug Discoverymentioning
confidence: 94%
“…In 1974 Cama, Christensen, and Guthikonda at Merck reported fully synthetic routes to "carbacephalosporin" and "oxacephalosporin" analogs replacing the sulfur atom within the bicyclic core of cephalothin (a first-generation cephalosporin), by a carbon atom and an oxygen atom, respectively (Figure 7). [102] Crucially, these fully synthetic analogs exhibited biological activity that was comparable to cephalothin.…”
Section: Antibacterial Drug Discoverymentioning
confidence: 94%
“…I-Oxacefamandole (2) was also prepared I 9 3 2 and has worked at the Laboratories since 1 9 5 4 by the Merck group in a racemic form and reported to be twice as active as cefamandole. 5 The Beecham group6 has been interested in 1-oxacephems in connection with clavulanic acid and successful in the synthesis of optically active 1-oxacephems such as (3) from penicillins. We at Shionogi have also been interested in this type of nuclear analog of cephalosporins, since we anticipated that I-oxa compounds would be more reactive at the P-lactam carbonyl and more polar than the 1-thia congeners for increased antibacterial activity particularly against gramnegative bacteria.…”
Section: Ps-5mentioning
confidence: 99%
“…It turned out that enhancement of the activity was consistently observed by replacement of sulfur with oxygen in the cephalosporin or cephamycin nucleus, more significantly against gramnegative bacteria. Valuable information obtained from the structureactivity relationship study includes: (i) I-oxacephems with the 7p-arylmalonylamido side chains and the 3-heterocyclic thiomethyl substituents (4) showed the most favorable activity and expanded spectra, (ii) stability to /3-lactamases generally decreased for I-oxacephem derivatives as compared with the I-thia congeners, and (iii) this stability was much improved by introduction of a 7a-methoxy group as exemplified by the almost complete gram-negative spectra of 1-oxacephamycins ( 5 industrially feasible synthetic route to the I-oxacephamycin nucleus, compound 6059-s is now very promising as an excellent new agent against pathogenic infections. 6059-s will be marketed shortly as a new antibiotic and is the first example of a synthetic P-lactam which has an unnatural ring system.…”
Section: Ps-5mentioning
confidence: 99%
“…Synthesis of the racemic 5-oxacephalotin (1) and 5-oxacephamandol (2) by Merck scientists 1,2 has shown that the substitution of cephalosporin sulfur atom by the oxygen atom resulted in the same or higher antibiotic activity in comparison to the parent drug. A thorough investigation undertaken during late seventies by Shionogi Co.…”
Section: Introductionmentioning
confidence: 99%